Marine ecosystem services: Linking indicators to their classification. (February 2015) - Hattam, Caroline; Atkins, Jonathan P.; Beaumont, Nicola; Bӧrger, Tobias; Bӧhnke-Henrichs, Anne; Burdon, Daryl; Groot, Rudolf de; Hoefnagel, Ellen; Nunes, Paulo A.L.D.; Piwowarczyk, Joanna; Sastre, Sergio; Austen, Melanie C.
Highlights: Generic ecosystem service classification been tailored for the marine environment. Need for indicators of ecosystem services, functions and benefits is highlighted. Indicators were assessed for their relevance in application to the Dogger Bank. Lack of indicator specificity, spatial disconnect and uncertainty are challenging. Potential to apply ecosystem service indicators to positive effect is recognized. Abstract: There is a multitude of ecosystem service classifications available within the literature, each with its own advantages and drawbacks. Elements of them have been used to tailor a generic ecosystem service classification for the marine environment and then for a case study site within the North Sea: the Dogger Bank. Indicators for each of the ecosystem services, deemed relevant to the case study site, were identified. Each indicator was then assessed against a set of agreed criteria to ensure its relevance and applicability to environmental management. This paper identifies the need to distinguish between indicators of ecosystem services that are entirely ecological in nature (and largely reveal the potential of an ecosystem to provide ecosystem services), indicators for the ecological processes contributing to the delivery of these services, and indicators of benefits that reveal the realized human use or enjoyment of an ecosystem service. It highlights some of the difficulties faced in selecting meaningful indicators, such as problems of specificity, spatial disconnect and the considerable uncertainty about marine species, habitats and the processes, functions and services they contribute to.